Developing Interactive Multimedia CD-based Teaching Materials for Teaching Arabic Skill at Arabic Education Department of Islamic State University Sunan Ampel Surabaya - Muflihah, Muflihah; Aziz, Husain (IAIN Samarinda, 2018)
The development of interactive multimedia CD-based teaching materials is urgent because the learning process in the Arabic Education Department is not 100% done as expected. This can be seen from some indicators that have not been achieved in the teaching and learning process. First, the lecturers teaching the same courses of Arabic language skills do not have the same standards of the competencies that students need to achieve, the learning objectives of each meeting and the assessment. Second, the use of interactive multimedia CDs have not been widely used by all lecturers of Arabic language skills. Third, there was no standard of teaching material used by some lecturers who teach the courses of Arabic language skills despite the findings from previous studies that show 25% of students have general high schools background which cause disparate abilities among students in the department. This study is a reseach and development adopting Sugiono’s development stages combined with ADDIE design model and the ASSURE design model which is then termed as ADDIERE design. This study uses mixed qualitative and quantitative methods. The results of this study are the following. First, there is a set of teaching materials comprising a validated and empirically-proven efective an interactive multimedia CD and book. The book consists of 12 chapters with each covers four language skills. The CD combines autoplay, wondershare quiz creator, record, Arabic pad tool and text media, audio and images.